2014
DOI: 10.1088/0022-3727/47/8/085203
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of absolute CO number densities in CH3F/O2plasmas by optical emission self-actinometry

Abstract: CH 3 F/O 2 inductively coupled plasmas at 10 mTorr were investigated using optical emission spectroscopy. A 'self-actinometry' method was developed to measure the absolute number density of CO that formed in reactions following dissociation of CH 3 F and O 2 in the plasma. In this method, small amounts of CO were added to the plasma, leading to small increases in the CO emission intensity. By carefully accounting for small perturbations to the plasma electron density and/or electron energy distribution, and by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Previously, we reported a 'self-actinometry' method that can be used to obtain absolute number densities of stable species in low pressure plasmas. N 2 and CO number densities were obtained in NH 3 and CH 3 F/O 2 plasmas [28,29], respectively, and were verified by independent spectroscopic measurements. In this study, self-actinometry was demonstrated under the more complex conditions encountered in atmospheric pressure plasmas.…”
Section: Introductionmentioning
confidence: 55%
“…Previously, we reported a 'self-actinometry' method that can be used to obtain absolute number densities of stable species in low pressure plasmas. N 2 and CO number densities were obtained in NH 3 and CH 3 F/O 2 plasmas [28,29], respectively, and were verified by independent spectroscopic measurements. In this study, self-actinometry was demonstrated under the more complex conditions encountered in atmospheric pressure plasmas.…”
Section: Introductionmentioning
confidence: 55%
“…The reason is that other collisional processes are trivial and the density of metastables is too low to make a significant contribution to the excitation of the excited species under these conditions [9][10][11]. In a corona model for these levels, we have the electron-impact excitation from the ground-state atom, Ar(gs) + e Ar(2p1 ) + e (1) and the spontaneous radiation, Ar(2p 1 )Ar(1s 2 ) + hv…”
Section: Icp Rf Dischargementioning
confidence: 99%
“…In order to understand the plasma chemistry, various plasma process diagnostic tools such as OES and Langmuir probe have been developed to quantify the concentration of reactive species in the plasma [1]. Because it is non-intrusive, inexpensive, and can be easily incorporated into an existing plasma reactor, the OES quickly gains popularity in the microelectronics industry for monitoring the plasma processing.…”
Section: Introductionmentioning
confidence: 99%